Genocide and Political Destruction in Tigray: The Imperative for Systemic Transformation - Muauz Gidey Alemu (Goodwood Publishing, 2024)
Purpose: This study aims to severe governance and public service challenges in the Tigray region of Ethiopia following genocide and political destruction, aiming to analyze the impact of the conflict on governance structures and advocate for transformative frameworks. Research Methodology: A qualitative survey involving 2,280 respondents were conducted using systematic random sampling and snowballing, with data collected through semi-structured interviews, focus group discussions, and field observations, analyzed using ATLAS.ti version 9. Results: The findings reveal significant gaps between public expectations and government performance, highlighting governance collapse, political instability, declining public services, and the long-term institutional damage that perpetuates social conflict and societal deterioration. Conclusions: Tigray is experiencing a deep governance and post-conflict crisis marked by weak institutions, political interference, lack of accountability, socio-economic inequality, and limited public trust, highlighting the urgent need for inclusive governance reforms, equitable development, and sustainable peacebuilding efforts. Limitations: This study emphasizes the importance of governance and political transformation that strengthens accountability, transparency, and citizen participation to support Tigray’s recovery, sustainable development, and social cohesion. Contributions: This study contributes to the theoretical and empirical understanding of the impact of genocide on governance and politics, particularly in relation to post-genocide societal and institutional transformation. Novelty: The novelty of this study lies in its focus on the governance challenges faced by the Interim Regional Administration in post-genocidal Tigray, particularly its capacity to implement inclusive governance reforms amid political fragmentation and institutional crises.